The practicality of popular scientific books on Moraceae plant ethnobotany case study at KHDTK ULM - Nurul Wahdatun Nufus; Yudi Firmanul Arifin; Dharmono Dharmono (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2022)
Cultural heritage in an area that is unique is one step in preserving it so that it can be used as a source of learning based on local potential in contextual learning developed in popular scientific book teaching materials. This development research entitled "Ethnobotany of Moraceae Plants Case Study at KHDTK ULM" aims to examine the practicality of the contents of the BIP, the practicality of expectations and the actual of BIP. The method in developing this research is to lead to formative evaluation by Tessmer. The results of the research on the readability test got very good criteria with an average value of 94.23%, in addition, the results of the BIP implementation test with an average value of 95.18% so that it can be grouped into very good criteria and the results of student responses show the average score BIP is 96.15% so it can be grouped into very practical criteria. This shows that a popular scientific book with the title "Plant Ethnobotany Moraceae case study at KHDTK ULM" is very practical to use and attracts students' reading interest in Ethnobotany learning.Abstrak Warisan budaya pada suatu daerah yang bersifat khas yaitu salah satu langkah dalam melestarikannya sehingga dapat dimanfaatkan sebagai sumber belajar berbasis potensi lokal dalam pembelajaran kontekstual yang dikembangkan dalam bahan ajar buku ilmiah populer. Penelitian pengembangan ini berjudul “Etnobotani Tumbuhan Moraceae Studi kasus di KHDTK ULM” memiliki tujuan untuk menguji kepraktisan isi BIP, kepraktisan harapan dan aktual BIP. Metode dalam pengembangan penelitian ini yaitu menggarah pada evaluasi formatif oleh Tessmer. Hasil penelitian pada uji keterbacaan mendapatkan kriteria sangat baik dengan nilai rata-rata 94,23%, selain itu, hasil uji keterlaksanaan BIP dengan nilai rata-rata 95.18% sehingga dapat dikelompokan dalam kriteria sangat baik dan hasil respon mahasiswa menunjukan hasil nilai rata-rata BIP yaitu 96,15% sehingga dapat dikelompokan dalam kriteria sangat praktis. Hal tersebut menunjukan bahwa buku ilmiah populer dengan judul “Etnobotani Tumbuhan Moraceae studi kasus di KHDTK ULM” sangat praktis digunakan dan menarik minat baca mahasiswa dalam pembelajaran Etnobotani.